Effect of different temperature on burning peat soil / Amir Nur Rahim Abd Aziz - Abd Aziz, Amir Nur Rahim (Faculty of Plantation and Agrotechnology, 2015)
Smoldering wildfires propagate slowly through surface of organic layers of the soil and severely affect the soil, producing physical, chemical and biological changes. These effects are caused by the prolonged heating and the large loss of soil mass and chemical properties are documented in the literature. This paper attempts to understand the effect of different temperature on peat soil (without burning, 100°c, 200°c, 300°c, 400°c, and 500°c) on volume soil loss, nutrient (N, P, K, Mg, Ca, Mn) and pH. 18 samples treatments are test and 3 replication for each temperature. The soil sample obtains at Felcra seri Mendapat and the analysis is done at UiTM Jasin Laboratory. Volume of soil loss is record after bum in Muffle Furnace. In addition, the nutrient analysis tests with ICP-OES (Inductively Couple Plasma-Optical Emission Spectrometry) for each of temperature. In order to analyse the nutrient, the sample were extracted first. For the third test, is performing using pH meter with the appropriate electrode. Volume soil loss, nutrient, and pH showed different response towards different temperature. Peat volumes will be lost since the fire consumed the peat soil. This result decreases the depth of plant soil due to conversion of organic matter to carbon dioxide (C0²). The pH of peat soil also shows the trend of increasing, but in moderate increasing. Finally, the regenerative aspect of different temperature is discussed.